Integrating Fintech and Digital Innovation in Climate Finance - Sawagvudcharee, Ousanee; Vohra, Simran (My University, 2026)
The long-term sustainability of climate finance depends on comprehending and managing risk and resilience. Due to the excessive levels of environmental degradation and climate change caused by human activity, there has been a recent surge in international efforts to promote environmental sustainability, eco-friendliness, and ecosystems and mitigate climate change. The purpose of this study is to learn more about how Fintech and digital innovations can be integrated into client finance. “How should Fintech and digital innovations be integrated in climate finance for global perspectives?” is emphasized. The triangulation approach was employed to enhance the validity, credibility, and completeness of a study’s findings. The document technique and non-participant observation were used to collect data. Critical analysis, content analysis, and thematic coding techniques were used. The findings demonstrate that information systems (IS), including information technology (IT), are necessary for integrating fintech and digital innovations in climate funding for global perspectives in all other economic sectors, including the financial industry. Ecological sustainability is a major worry for authorities globally due to the disastrous consequences. Fintech, digital innovations, and climate funding are some of the new strategies required to combat climate change, ethical governance, and related environmental challenges. Fintech and other digital advancements include new methods of product development and company operations that impact businesses and services. Fintech innovations like artificial intelligence (AI) and technology have the potential to significantly alter the climate funding industry by enhancing accessibility, reliability, safety, and transparency. Fintech, or financial technology, has the potential to improve service delivery and address societal issues like water sustainability.
Keywords: Digital innovations; Fintech; Information systems; Information technology